PARENTING IN CONFLICT – PARENTAL ALIENATION: NETNOGRAPHIC RESEARCH - ROSZAK, MAGDALENA (Society Register, 2021)
Parental alienation is a phenomenon that appears after the divorce or break-up in a situation, where there is high conflict between the separating parents accompanying the termination of the relationship. It includes actions intentionally taken by one of the sides, who is seeking to distort the relationship between the child and the other parent. As a result of the alienation, the child starts to excessively prefer the custodial parent and intensively reject the non-custodial parent. The discussion concerning parental alienation was initiated by Richard Gardner, a psychiatrist, who introduced the idea of PAS ‘parental alienation syndrome’. His concept was widely commented by its supporters as well as by sceptics and opponents, as a result of which its modified version, PA ‘parental alienation’, was developed. Published research concerning the subject can be found in English-language scientific articles as early as in 1998. However, in Polish academic literature parental alienation is almost non-existent. The objective of this article is to open a discussion on this subject. Apart from theoretical analysis of the phenomenon, the narratives of parents who believe to experience PA were analysed. The analysis regarded aspects such as: definition, characteristics and sources of parental alienation. The article analyses also actions, which are the alienated parents’ reactions to PA. The performed analysis was of netnographic nature.